Pengaruh Green Product, Green Advertising, Dan Green Brand Image Terhadap Keputusan Pembelian Dengan Consumer Attitude Sebagai Variabel Mediasi : Buying decision, Green Product Attributes, Green Advertising, Green Brand Image, Consumer Attitude - Augtiah, Imfrianti; Ihwan Susila; Wiyadi (Universitas Muhammadiyah Surakarta, 2022)
The objectives of this study were to determine the effect of green product attributes on purchasing decisions mediated by consumer attitude, to determine the effect of green advertising on purchasing decisions mediated by consumer attitude, to determine the effect of green brand image on purchasing decisions. mediated by consumer attitude, and knowing the effect of consumer attitude towards purchasing decisions. This study used a quantitative approach with an associative design. The data collection technique used in this study was questionnaire distribution. Hypothesis testing in this study was carried out using path analysis with the help of SPSS and mediation analysis with SPSS macro PROCESS version V3.0 (Hayes, 2013). The results showed Consumer Attitude significantly mediates the effect of green product attributes on purchasing decisions, Consumer Attitude significantly mediates the effect of green advertising on purchasing decisions, Consumer Attitude significantly mediates the effect of green brand image on purchasing decisions, and Consumer attitude has a positive and significant effect on purchasing decisions.